Comment on "A fully nonlinear implicit model for wave interactions with submerged structures in forced or free motion" by Guerber et al. (2012). (February 2015) - Wang, Lixian; Tang, Hui
Abstract: This paper reports a problem in the simulation of transient oscillation of a freely heaving cylinder appearing in Guerber et al. (2012)'s recent paper A fully nonlinear implicit model for wave interactions with submerged structures in forced or free motion . The problem is confirmed through a comparison study using an independent two-dimensional fully nonlinear numerical wave tank. The reason may come from the part solving the acceleration potential. In the end, the influence of this problem to the other results presented in the same paper is assessed.